Sociodemographic Profile, Genotype, and Response to Therapy in Hepatitis C Virus Infection: A Brief Report from Himachal Pradesh - Sharma, Brij; Sharma, Vineeta; Kumar, Rajesh; Sharma, Rajesh; Bodh, Vishal; Chauhan, Ashish; Sachdeva, Amit; Majeed, Tahir; Bilal, Mir; Sharma, Dikshant (Journal of Gastrointestinal Infections, 2023)
Introduction Hepatitis C virus (HCV) infection is a major cause of liver disease worldwide. There is no data on sociodemographic profile, risk factors, genotype, and response to therapy of HCV infection from Himachal Pradesh.Methods In this single-center study, we retrospectively analyzed data from HCV-infected patients treated with new oral direct-acting antiviral drugs from September 2019 to March 2022. Data on the sociodemographic profile of HCV-infected patients, along with risk factors for its transmission, HCV genotype, and response to therapy, was analyzed.Results A total of 189 patients were included, with a mean age of 30.9 ± 13.8 years. Most were males and were students. Predominant risk factor for HCV transmission was intravenous drug use (61.4%), tattooing (11.7%), and hemodialysis (11.1%). A majority of the patients were students (72%). The predominant genotype was GT 3. Most (95.2%) patients were without cirrhosis, so sofosbuvir plus daclatasvir for 12 weeks was the most common regimen used. Sustained virological response was achieved in 94.7% of patients.Conclusion This study, alarmingly, shows that intravenous drug users and tattooing are important risk factors for HCV infection in Himachal Pradesh. Further, students were the most frequently infected group.
Keywords: hepatitis C virus; direct acting antiviral; hepatitis C virus genotype; National Viral Hepatitis Control Program